2019
DOI: 10.1002/yea.3430
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of yeasts in the soil adjacent to fruit trees of the Rosaceae family

Abstract: Yeasts are common constituents of different types of soil. Their diversity depends on the season, the type and depth of the soil, the plant species, and the locality. In this study, diversity of yeasts isolated from the soil adjacent to five fruit trees (apple, appricot, peach, pear, and plum) in two localities (in Slovakia) in four sampling periods was examined. Our results demonstrated differences in the species richness and evenness among the yeast populations, which inhabited the soil beneath individual fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
(69 reference statements)
2
17
1
Order By: Relevance
“…The samples collected in this study were from rhizosphere soil at the ripening stage of Hami melon, which may also account for the higher abundance of basidiomycetous yeasts in this study. Additionally, the rare yeast found in this study accounted for approximately 54.79% of the yeast species in all soil samples of Hami melon, a value within the range of the proportion of rare yeast isolated by other studies from fruit trees, forests, grasslands, and shrub soils [37,50,51]. Tausonia pullulans, which was detected in this study, produces Indole-3-acetic acid (IAA), which could be developed for future applications in promoting plant growth [11,52,53]; Filobasidium_magnum, Naganishia_albida, and Cutaneotrichosporon_curvatus belong to three of the dominant species in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The samples collected in this study were from rhizosphere soil at the ripening stage of Hami melon, which may also account for the higher abundance of basidiomycetous yeasts in this study. Additionally, the rare yeast found in this study accounted for approximately 54.79% of the yeast species in all soil samples of Hami melon, a value within the range of the proportion of rare yeast isolated by other studies from fruit trees, forests, grasslands, and shrub soils [37,50,51]. Tausonia pullulans, which was detected in this study, produces Indole-3-acetic acid (IAA), which could be developed for future applications in promoting plant growth [11,52,53]; Filobasidium_magnum, Naganishia_albida, and Cutaneotrichosporon_curvatus belong to three of the dominant species in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The larger number of soil yeasts isolated in the presence of fungicides may reflect the higher species diversity in soil as compared to that in the phyllosphere [42]. Soil acts as a reservoir of phyllosphere yeasts and provides a plethora of niches with different nutrients and substrates that soil yeasts can thrive in [43][44][45][46]. It is also possible that some of the many soil fungi bind or inactivate fungicides, thereby reducing their effective concentrations and thus allowing otherwise sensitive species to be isolated.…”
Section: Discussionmentioning
confidence: 99%
“…A. pullulans was, by far, the most frequent species (76 isolates), isolated in the presence of seven out of the eight antifungal agents tested and found in all the four sample sources (soil, leaves, fruits, and flowers). This highlights the ubiquitous nature of A. pullulans and its ability to thrive in different habitats (e.g., soil, leaves, flowers, and fruits) and environmental conditions (e.g., hypersaline habitats, glaciers, arid conditions, and radiation sites) due to the presence of genes that confer stress tolerance [ 34 , 46 , 51 , 52 , 53 , 54 , 55 ]. Similarly, M. pulcherrima, C. laurentii, C. misumaiensis, and S. metaroseus are also commonly occurring and frequently isolated from the leaves of various trees, fruits, and soils of both agricultural and wild habitats, and can tolerate extreme conditions [ 43 , 46 , 51 , 56 , 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruits are an important habitat for different groups of wild yeasts. Fruit microbiology has already been addressed by several authors from different countries [16,35,52,53]. Buenrostro-Figueroa et al [54] reported that the species Candida kefir, Kluyveromyces bulgaricus, Kluyveromyces fragilis, Candida macedoniensis, and Candida tropicalis have been isolated from mango fruit.…”
Section: Yeast Community Compositions Of Different Samplesmentioning
confidence: 99%